Contact Lens Complications of Patients Visiting a University Eye Clinic. - Farnon, Dr Niall; Boodram, Cassandra; Hilaire, Shanik (Faculty of Medical Sciences, The UWI, St. Augustine Campus, Trinidad and Tobago, 2023)
Objective: To determine the percentage of patients that experience contact lens complications at the University of the West Indies (UWI) Optometry Clinic as well as to establish and assess common physiological complications of the cornea and conjunctiva that occur in those that wear either soft, rigid and scleral contact lenses, of that percentage. Methods: Contact lens wearers of the clinic were identified, contacted via telephone and asked if they would be interested in participating in the study. Once they agreed, participants visited the clinic wearing their contact lenses two hours prior as instructed. Participants were required to give verbal and written consent before completing a questionnaire. The anterior part of the eye was observed using a slit lamp and times 10, 16 and 25 magnifications were used to view the conjunctiva and cornea appropriately. The data collected was analysed using SPSS. Results: The study included 19 participants, mainly females aged 18-25 who were mostly wearing soft, daily disposable contact lenses. There were three scleral patients and no RGP patients participating in the research. The most common symptom reported was dry eyes, and the most common complication was hyperaemia. All participants reported washing their hands before inserting lenses but a few participants were still sleeping and showering in their lenses, overwearing them, and not cleaning or disposing of their lens cases within the recommended time. Conclusion: Patients' age and compliance were two major factors that contributed to patients having or not having complications. Patient knowledge of contact lens complications and proper care practices did not influence how patients cared for their contact lenses.